PENGARUH ORGANISASI INFORMASI TERHADAP PELESTARIAN BAHAN PUSTAKA DALAM RUANG LINGKUP PERPUSTAKAAN PERGURUAN TINGGI - Diaz Ilyasa (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
The library is a place where events from information transactions occur. Along with the development of information technology, the library is constantly making adjustments in order to satisfy users with its information services. Information in the library is processed through information organization activities, library materials are a form of information. Library materials in college libraries are supposed to be preserved, but in fact many library materials are not well preserved because they are not supported by the activities of information organizations. The purpose of this study is to determine the influence of information organizations on the preservation of library materials within the scope of college libraries and to know information organizations as preservation of library materials in college libraries. The data collection techniques used in this study were observation, interviews, and literature review. The result of this research is that information organization activities in higher education libraries affect the preservation of library materials and information organization activities in the scope of higher education libraries as an effort to preserve library materials need to be carried out as soon as possible, including as a supporter of the development of science and a supporter of the Tri Dharma of higher education.